Biological knowledge combined with innovative engineering to reduce power plant impingement of horseshoe crabs - Claire Crowley-McIntyre; Berlynna Heres; H. Jane Brockmann; Ryan Gandy; Lisa Gregg (PLoS ONE, 2025)
Electric generating plants (power plants) are often subject to regulatory requirements to comply with the impingement mortality reduction standards of Section 316(b) of the federal Clean Water Act. In 2014, a power plant located on the Northern Indian River Lagoon (NIRL) in Florida, identified impingement of adult American horseshoe crabs (Limulus polyphemus, Linneaus, hereafter; horseshoe crabs) at the intake bar screens located in the plant intake canal. In November of 2014 the plant installed a prototype fence to mitigate horseshoe crab impingement but found that an average of 50,188 horseshoe crabs per year were still being impinged. In 2015, the plant sought to collaborate with the Florida Fish and Wildlife Conservation Commission (FWC) and University of Florida to modify the fence to reduce the impingement of horseshoe crabs, while still allowing manatees access to thermal refugia and to provide unobstructed passage of sea turtles and fuel barges. The plant and collaborators worked to improve the design with consideration of the structural orientation, material composition, and natural horseshoe crab behavior. In November 2017, the plant installed the improved design, a permanently submerged deterrent wall across the width of the intake channel that achieved the goal of reducing horseshoe crab impingement while allowing the free movement of manatees, sea turtles, and fuel barges. Continued monitoring and maintenance of the intake system and deterrent wall shows horseshoe crab impingement was reduced by 97.3% to an average yearly impingement of 647.7 horseshoe crabs with final wall installation. This collaborative engineering approach illustrates the effectiveness of well-designed and maintained barriers in reducing horseshoe crab impingement while allowing compliance with regulatory changes without disruption to operations.